STUDI PERSPEKTIF SISWA TERHADAP EFEKTIVITAS PEMBELAJARAN MATEMATIKA DENGAN PENERAPAN CHATGPT - Auna, Hariyanto S. Auna; Hamzah, Nuriyati (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2024)
Abstract. The utilization of individually tailored learning systems facilitated by artificial intelligence (AI) yields substantial advantages in comprehending mathematical concepts among students. Through the capability to adapt the learning pace to each student's comprehension level, AI fosters a personalized and efficacious learning experience. This enables students to concentrate on areas demanding more attention, thereby enhancing their comfort and confidence in the process of learning mathematics. The integration of this technology not only expedites material assimilation but also establishes an environment conducive to the holistic development of mathematical skills. This research proposes an examination that seeks to scrutinize the perspective of artificial intelligence, specifically focusing on the application of ChatGPT, in mathematics education at SMA Negeri 6 Gorontalo. The research methodology employed involves descriptive analysis through the distribution of questionnaires to students. These questionnaires are crafted to probe their opinions on the efficacy of ChatGPT in enhancing comprehension and engagement in mathematics learning. Anticipated outcomes of the analysis aim to furnish profound insights into the repercussions of integrating artificial intelligence in the realm of mathematics education at the secondary school level. The research findings revealed a disjunction between the satisfaction levels of SMA Negeri 6 Gorontalo students with ChatGPT in mathematics learning and the infrequent utilization of the tool in schools. This discrepancy necessitates a thorough evaluation and policy adjustments, encompassing flexibility in smartphone usage regulations, improvements in internet connectivity, and a proactive approach to enhance student participation in the assimilation of ChatGPT into the learning process. Based on the research results, it appears that there is a gap between the level of student satisfaction with the use of ChatGPT in mathematics learning and the frequency of use which is less frequent in school. Although some students stated that they were satisfied with using ChatGPT, the majority indicated that they rarely used the application. Therefore, it is concluded that there are several barriers or inhibiting factors that may influence the low frequency of use in the school environment. Abstrak. Pemanfaatan sistem pembelajaran yang dirancang secara individual yang difasilitasi oleh kecerdasan buatan (AI) menghasilkan keuntungan besar dalam pemahaman konsep matematika di kalangan siswa. Melalui kemampuan untuk menyesuaikan kecepatan pembelajaran dengan tingkat pemahaman setiap siswa, AI menumbuhkan pengalaman belajar yang dipersonalisasi dan efektif. Hal ini memungkinkan siswa untuk berkonsentrasi pada bidang yang memerlukan perhatian lebih, sehingga meningkatkan kenyamanan dan kepercayaan diri mereka dalam proses belajar matematika. Integrasi teknologi ini tidak hanya mempercepat asimilasi materi tetapi juga menciptakan lingkungan yang kondusif bagi pengembangan keterampilan matematika secara holistik. Penelitian ini mengusulkan suatu kajian yang berupaya mencermati perspektif kecerdasan buatan, khususnya yang berfokus pada penerapan ChatGPT dalam pendidikan matematika di SMA Negeri 6 Gorontalo. Metodologi penelitian yang digunakan meliputi analisis deskriptif. Penelitian ini dibuat untuk menyelidiki pendapat mereka tentang kemanjuran ChatGPT dalam meningkatkan pemahaman dan keterlibatan dalam pembelajaran matematika. Hasil analisis yang diharapkan bertujuan untuk memberikan wawasan mendalam tentang dampak pengintegrasian kecerdasan buatan dalam bidang pendidikan matematika di tingkat sekolah menengah. Temuan penelitian menunjukkan adanya perbedaan antara tingkat kepuasan siswa SMA Negeri 6 Gorontalo terhadap ChatGPT dalam pembelajaran matematika dan jarangnya pemanfaatan alat tersebut di sekolah. Kesenjangan ini memerlukan evaluasi menyeluruh dan penyesuaian kebijakan, yang mencakup fleksibilitas peraturan penggunaan ponsel cerdas, peningkatan konektivitas internet, dan pendekatan proaktif untuk meningkatkan partisipasi siswa dalam asimilasi ChatGPT ke dalam proses pembelajaran. Berdasarkan hasil penelitian, terlihat adanya kesenjangan antara tingkat kepuasan siswa terhadap penggunaan ChatGPT dalam pembelajaran matematika dan frekuensi penggunaan yang kurang sering di sekolah. Meskipun sebagian siswa menyatakan puas dengan penggunaan ChatGPT, namun mayoritas mengindikasikan bahwa mereka jarang menggunakan aplikasi tersebut. Oleh karena itu, disimpulkan bahwa terdapat beberapa hambatan atau faktor penghambat yang mungkin mempengaruhi rendahnya frekuensi penggunaan di lingkungan sekolah.